Women Pregnancy amids Covid-19: Understanding Vulnerability, Developing Vaccine Strategy, and Capacity in Palembang - Siti Anisyah (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
Women in pregnancy have special needs and may require different forms of physical, social, mental, and emotional support than others because they are very vulnerable to death, illness and injury during the Covid-19 pandemic. This article examines how the government plans to prepare some strategies and capacity to ensure pregnant women's safety during the Covid-19 pandemic in Palembang. We conducted a field study with essential questions in assessing the vaccination program for pregnant women, government, hospitals, print news, and online about the distribution of services and the availability of vaccination for pregnant woman are delaying. In this article, we found a significant disruption to the practice of vaccination of pregnant women in the city of Palembang during the COVID-19 pandemic. This is not only because of the closure of health services but also because of the lack of supply of vaccine distribution for pregnant women, so the vaccination program for pregnant women has been delayed. We urge the government to strengthen the strategy and capacity to ensure that vaccination services for pregnant women are available in the city of Palembang because even though the Covid-19 pandemic is currently sloping, there is still a possibility that it will rise again.